The effect of 10% alpha-tocopherol solution and 5% grape seed extract on the microhardness and shear bond strength to bleached dentin - Manvi Srivastava; Ramakrishna Yeluri (Wolters Kluwer Medknow Publications, 2021)
Background: The aim of the study was to evaluate the effect of 10% alpha-tocopherol and 5% grape seed extract on the microhardness and shear bond strength (SBS) to bleached human dentin. Materials and Methods: This in vitro study was done on 200 extracted premolars which were decoronated and grinded to get flat dentin surface occlusaly. They were divided into four groups: (a) bleaching, (b) bleaching and application of alpha-tocopherol, (c) bleaching and application of grape seed extract, and (d) control. Groups were further subdivided into Subgroups I and II (n = 30) based on storage period before building with composite and were then tested for microhardness and SBS determination. The data thus obtained was subjected to statistical analysis which was performed using ANOVA test and post hoc Tukey's test. The significance for the entire statistical test was predetermined at P < 0.05. Results: The results showed that the microhardness values were minimum in Group A (immediately after bleaching) and maximum in control group. Comparison of data using one-way ANOVA showed that the P value was highly significant (P < 0.001) among the groups. The intergroup comparison of SBS using post hoc Tukey's tests revealed that the P value was significant (P < 0.05) when the comparison was done between the Group A and Group C and Group B with Group D immediately after bleaching. Conclusion: Adverse effects of bleaching can be reversed with the application of 10% alpha-tocopherol and 5% grape seed extract over the dentinal surface microhardness and SBS.